A comparison between axillary brachial plexus block and elbow block using ultrasound in patients undergoing surgeries of wrist and hand - Biswas, Amit Kumar; Das, Debojyoti; Rahman, Sarfraaz; Maji, Sandip; Sinha , Sandip; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2023)
Background: Both the axillary brachial block and elbow block are easy to learn and perform. Elbow block was previously used to as a rescue block to supplement the inadequacy of proximal nerve plexus block. Recently, elbow block is emerging as a primary anesthetic technique for wrist and hand surgeries. However, no such study in Indian scenario exists comparing axillary brachial plexus block and elbow block using ultrasound (US) guidance during wrist and hand surgeries. Aims and Objectives: The present study was designed to compare axillary brachial plexus block and elbow block for hand and wrist surgery in terms of duration of post-operative analgesia (Primary outcome), procedure times, other characteristics of block, patient satisfaction, and adverse events. Materials and Methods: This open-label parallel-group randomized study was performed in 78 adults, aged 18–70 years, ASA I-II, undergoing elective surgeries of wrist and hand. The patients were randomly allocated into two equal groups to receive either axillary brachial plexus block (Group A, n=39) or elbow block (Group B, n=39), both under US guidance. The time to first rescue analgesia was the primary outcome measure. Other outcome measures were different characteristics of nerve blocks, procedure duration, 24-h analgesic consumption, patient’s satisfaction score, and adverse events. Results: The time to first analgesic administration was considerably higher in axillary block compared with elbow block (15 vs. 14 h, P<0.001). However, the post-operative analgesia with elbow block was not clinically insignificant. The onset of blocks was faster with axillary block compared with elbow block (sensory block 15 vs. 24 min, P<0.001; motor block 20 vs. 30 min, P<0.001). Overall, a higher number of patients were more satisfied with elbow block. Conclusion: Using US, elbow block can be a better alternative to axillary block for hand surgeries in terms of sufficient post-operative analgesia, comparatively shorter motor block, and better patient satisfaction.